Structure and floristic of secondary and old growth stands in lowland Costa Rica - Guariguata, Manuel R.; Chazdon, R.L.; Denslow, J.S.; Dupuy, J.M.; Anderson, L. (1997)
The study characterised stand structure and floristic composition of woody life forms in three, 16-18 year old secondary stands that regenerated after pasture abandonment, and three nearby old-growth stands of tropical rainforest in lowland Costa Rica. Basal area and stem density for each of four plant size classes (seedling, saplings, treelets, trees) were similar among stand types, but density of adult canopy palms (individuals over 10 cm dbh), was lower in the secondary stands. The observed rapid woody regrowth, compared to other published studies in the lowland neotropics, can be attributed to moderate land use and possibly to the influence of nutrient-rich volcanic soils in the study area. Overall, plant species richness was lower in the secondary stands, but this difference was less pronounced in the smallest size classes (seedlings, saplings). Median percentage similarity of all pairwise stand comparisons showed that floristic composition of saplings (stems over 1 m tall and over 5 cm dbh) was more similar between secondary and old-growth stands than for trees (stems over 10 cm dbh). Because the potential value of secondary forests in conserving woody plant diversity appears highest for the young size classes, we suggest that further studies on floristic composition, especially those addressing the dynamics of the understorey component, are needed to refine our understanding of the role of this natural resource in the maintenance of plant biodiversity in disturbed landscapes.